Early death from childhood cancer: First medical record‐level analysis reveals insights on diagnostic timing and cause of death - Katherine T. Lind; Elizabeth Molina; Amy Mellies; Kami Wolfe Schneider; William Daley; Adam L. Green (Cancer Medicine, 2023)
Abstract Background Approximately 7.5% of pediatric cancer deaths occur in the first 30 days post diagnosis, termed early death (ED). Previous database‐level analyses identified increased ED in Black/Hispanic patients, infants, late adolescents, those in poverty, and with specific diagnoses. Socioeconomic and clinical risk factors have never been assessed at the medical record level and are poorly understood. Methods We completed a retrospective case–control study of oncology patients diagnosed from 1995 to 2016 at Children's Hospital Colorado. The ED group (n = 45) was compared to a non‐early death (NED) group surviving >31 days, randomly selected from the same cohort (n = 44). Medical records and death certificates were manually reviewed for sociodemographic and clinical information to identify risk factors for ED. Results We identified increased ED risk in central nervous system (CNS) tumors and, specifically, high‐grade glioma and atypical teratoid/rhabdoid tumor. There was prolonged time from symptom onset to seeking care in the ED group (29.4 vs. 9.8 days) with similar time courses to diagnosis thereafter. Cause of death was most commonly from tumor progression in brain/CNS tumors and infection in hematologic malignancies. Conclusions In this first medical record‐level analysis of ED, we identified socioeconomic and clinical risk factors. ED was associated with longer time from first symptoms to presentation, suggesting that delayed presentation may be an addressable risk factor. Many individual patient‐level risk factors, including socioeconomic measures and barriers to care, were unable to be assessed through record review, highlighting the need for a prospective study to understand and address childhood cancer ED.